2019
DOI: 10.1103/physrevd.100.016017
|View full text |Cite
|
Sign up to set email alerts
|

Anapole dark matter via vector boson fusion processes at the LHC

Abstract: Dark matter that is electrically neutral but couples to the electromagnetic current through higherdimensional operators constitutes an interesting class of models. We investigate this class of models at the Large Hadron Collider, focusing on the anapole moment operator in an effective field theory (EFT) framework, and utilizing the vector boson fusion (VBF) topology. Assuming proton-proton collisions at √ s = 13 TeV, we present the VBF anapole dark matter (ADM) cross sections and kinematic distributions as fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Firstly, for dark matter masses above m W , the W + W − annihilation channel plays an important role in fixing the thermal relic abundance. Secondly, a recent phenomenological study [37] has found the VBF process to be a sensitive probe of 'anapole' dark matter, which corresponds to the photon version of the C A operator in Eq. (2).…”
Section: Dark Matter Scattering With W Bosonsmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, for dark matter masses above m W , the W + W − annihilation channel plays an important role in fixing the thermal relic abundance. Secondly, a recent phenomenological study [37] has found the VBF process to be a sensitive probe of 'anapole' dark matter, which corresponds to the photon version of the C A operator in Eq. (2).…”
Section: Dark Matter Scattering With W Bosonsmentioning
confidence: 99%
“…Furthermore, the dark matter mass itself is a free parameter and determines the relevant scale for thermal freeze-out and indirect detection constraints. Electromagnetic form factors for dark matter have been considered in direct and indirect detection as well as at colliders over several decades of dark matter mass, extending into the TeV range [8][9][10][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, it is clear that the hypercharge form factors should be the appropriate EFT here, given that relevant energies can far exceed the electroweak scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VBF topology is particularly useful to search for new physics, see for instance [67][68][69][70][71][72][73][74][75]. It involves two high p T jets in the forward direction, located in opposite hemispheres of the detector.…”
Section: Searches With a Vector Boson Fusion Triggermentioning
confidence: 99%